Genetic association study of the rs10774671 variant of the OAS1 gene with the severity of COVID-19 in an Ecuadorian population.: Estudio de asociación genética de la variante rs10774671 del gen OAS1 con la severidad de COVID-19 en una población ecuatoriana. - Pilataxi , Kathya; Balarezo, Thalía; Chávez, Erik; Acosta , Camila; Peña, Ivonne Z.; Narváez, Katherin; Álvarez-Nava, Francisco (Investigación Clínica, 2024)
COVID-19 exhibits a wide range of phenotypic manifestations, from asymptomatic to severe phenotypes with fatal complications. The existence of risk factors cannot entirely explain the variance in the phenotypic variability of COVID-19. Genome-wide association analyses have identified target human genes related to virus transmission and the clinical phenotype observed in COVID-19 patients. Genetic variants on the OAS1 gene have been associated with innate immune processes (entry phase and viral replication in host cells). The A or G alleles of rs10774671 in OAS1 encode isoforms with different antiviral activities. One hundred COVID-19 patients were genotyped for the rs10774671 using RFLP-PCR (severe form, n = 43; asymptomatic-mild, n =57). The susceptibility of the two groups to the severe phenotype of COVID-19 was compared. The allele frequency for A was 0.8. The genotypic frequencies for AA and GG homozygotes were 0.62 and 0.02, respectively. A Hardy-Weinberg equilibrium deviation was found in both groups. No statistically significant as- sociations were found in genetic models adjusted for sex (for the additive model OR = 1.18, 95% CI = (0.53-2.61), p = 0.69). A relatively recent mix of different ethnic groups and sample size may influence these findings.